A MENGGAGAS HEGEMONI EPISTEMIK-KELEMBAGAAN: PERAN SHANGHAI COOPERATION ORGANIZATION DALAM PEMBANGUNAN : Indonesia - Elnathan, Andrew; Azis, Aswin Ariyanto (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This article examines how the Shanghai Cooperation Organization (SCO), treated as an organization rather than a mere aggregate, can catalyze Global South leadership in economic development. Building on Said’s Orientalism, Santos’s Epistemologies of the South, and Global South IR (Tickner & Smith), the study uses a qualitative literature review with meta-synthesis. Findings indicate a three-tier role: (1) at the level of values, the Shanghai Spirit advances solidarity and equality, shifting development discourse from Western universals to epistemic plurality; (2) at the level of instruments, initiatives such as a development bank signal an intra-South financing ecology less dependent on conditionalities; and (3) at the level of norms, the coalition diffuses best practices and broadens security–development. Conceptually, the coalition functions as a decolonial “contact zone,” translating local experience into standards and enabling leadership rather than coercive dominance. Implications include governance and metrics beyond GDP; limitations include reliance on secondary sources and the need for empirical tests.